Fenomena Sosial Mikro-Makro Nahdlatul Wathan Era Orde Baru - Jamiluddin, Jamiluddin (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2018)
This article discusses how Nahdlatul Wathan is prepared to care for the Islamic mission and the future of the country. Also include in some sub, this article examines the effort was done by Nahdlatul Wathan manifest his existence, for example, as system engineering organization that carefully conditioned with deep and widespread benefit standard. Study of integration efforts of the entire element, both micro as well as macro Nahdlatul Wathan became a staple part because that social phenomenon conspicuous in the dynamics of the Nahdlatul Wathan. Answering some doubts, trigger the interest analyze the awareness of Nahdlatul Wathan more conical in the post national tragedy, G-30-S PKI. In more detail, the author loads the perception ofNahdlatul Wathan positioning the national tragedy above as a threat of the prestige of Republic Indonesia. The author then observe that the Nahdlatul Wathan at the beginning of the new orde era as it has come to a turning point to do something for his country and nation without support of hope space "what is givenby Indonesia to Nahdlatul Wathan?". Nahdlatul Wathan in importance of optimizing his participation build a country, programmatically doing stages based on harakah was destabilizing the depend mechanism of the nation, especially the nahdliyin, so it is solid and firmly hold the national ideology as a manifestation of "hubbul Wathan" at once as a marker of religious settlement . These facts and phenomenon did not escape the spotlight in this article.